Intra-Arterial Tissue Plasminogen Activator for Central Retinal Artery Occlusion - Sobol EK (Dove Medical Press, 2021)
Ethan K Sobol,1,2 Yu Sakai,3 Danielle Wheelwright,3 Carl S Wilkins,1,2 Amanda Norchi,1 Michael G Fara,4 Christopher Kellner,3 James Chelnis,1 J Mocco,3 Richard B Rosen,1,2 Reade A De Leacy,3 Gareth MC Lema1,2 1Department of Ophthalmology, Icahn School of Medicine at Mount Sinai, New York, NY, 10029, USA; 2Department of Ophthalmology, New York Eye and Ear Infirmary of Mount Sinai, New York, NY, 10003, USA; 3Department of Neurosurgery, Icahn School of Medicine at Mount Sinai, New York, NY, 10029, USA; 4Department of Neurology, Icahn School of Medicine at Mount Sinai, New York, NY, 10029, USACorrespondence: Gareth MC LemaDepartment of Ophthalmology, Icahn School of Medicine at Mount Sinai, One Gustave L. Levy Place, New York, NY, 10029, USATel +1 212-241-0939Fax +1 212-824-2325Email gareth.lema@mssm.eduPurpose: To investigate the benefit of early intra-arterial tissue plasminogen activator (IAT) for treatment of central retinal artery occlusion (CRAO).Patients and Methods: Fifteen eyes of 15 patients presenting with acute CRAO were included in this retrospective consecutive interventional case series. Patients were excluded if treatment with IAT was not initiated within 12 hours. The diagnosis was confirmed by an ophthalmologist. IAT was performed via a transfemoral arterial approach. Tissue plasminogen activator (tPA) was infused into the ophthalmic artery in aliquots up to 3mg to a maximum of 22mg. Paracentesis was done at the ophthalmologist’s discretion. The primary outcome measure was visual acuity after three weeks. Adverse events were recorded during treatment and follow-up visits.Results: After treatment with IAT, there was a statistically significant improvement in visual acuity, with a mean change of − 0.76 (SD 0.91; range − 2.4 to 0.85) logMAR (p=0.006). Vision improved by 3 or more lines in 53%, and of these, the mean Snellen visual acuity improvement was > 6 lines. Notably, 4 patients (27%) improved from CF or worse to 20/80 or better. The mean dose of tPA used was 17mg and the mean time to treatment was 8.83 hours (range: 5.5 to 12 hours). There were no statistically significant differences based on time to treatment, dose of tPA, or use of a paracentesis. No major adverse events were recorded.Conclusion: IAT was safe and showed significant visual improvement in this small uncontrolled study. Larger studies and efforts to decrease time to treatment should be initiated to optimize outcomes.Keywords: CRAO, tPA, intervention, treatment, ophthalmic artery